Reality Check: Early Intervention in Gateway Courses - Barbara Brown (Academic Chairpersons Conference Proceedings, 2018)
Early each semester, most professors can identify which of their students may succeed and which may not, but they may not know the reasons why or how to respond. Systematic reporting on at-risk students can help both professors and students recognize performance issues and possibly intervene before it’s too late
Keywords: assessment; intervention; student success; accountability